Micropropagation, in-vitro conservation and genetic stability studies in pummelo (Citrus maxima) - KAUR, SUKHDEEP; MALIK, S K; CHOUDHARY, RAVISH; CHAUDHURY, REKHA; KUMAR, RAJEEV (The Indian Journal of Agricultural Sciences, 2019)
Pummelo (Citrus maxima L.) is a natural, mono-embryonic and a true fruit species of genus Citrus cultivated widely in India. The study aimed at developing in vitro technique for conservation of Citrus maxima germplasm using shoot tip and nodal section as explants. Various concentrations and combination of hormones were used for successful in-vitro conservation. The shoots sprouted within 9-20 days when inoculated on MS medium supplemented with 0.5 mg/l BAP + 0.1 mg/l NAA growth hormones and above 86% germination was obtained with maximum numbers of shoots (8) and nodes (8.67). Highest shoot elongation (82%) was observed in MS medium supplemented with concentration of 0.6 mg/l GA3 in combination with 0.2 mg/l BAP, shoot length ranged between 1.17 to 6.90 cm and the number of nodes was 2.33-8.33 per plantlet. 1/2 MS medium supplemented with 0.5 mg/l BAP +1.0 mg/l NAA along with 2.5 g phytagel showed best result for rooting (78.33%). The regenerated plantlets did not show any detectable morphological variation at genetic level as evidenced by SSR profiles of plantlets. The developed protocol can be successfully employed for large-scale multiplication and conservation of Pummelo germplasm.